Preparation of Reduced Graphene Oxide and Its Antibacterial Properties. (2017) - Navya Rani, M.; Ananda, S.; Rangappa, Dinesh
Abstract: There is a growing interest on the Graphene based nanomaterials for biomedical applications, due to their interesting antibacterial and microbial properties. Generally, graphene based nanomaterials are commonly prepared by chemical reduction method. Such graphene or reduced graphene sheets possess residual toxic reducing agent molecules, which are not suitable for the biomedical applications. In this regard, we report a facile phytochemical assisted reduction method to prepare reduced graphene oxide (RGO) using Marigold flower extract. The obtained product is characterized using different techniques such as, XRD, UV-Visible spectra, FTIR and SEM Techniques. The antibacterial property of the resultant product was tested against gram positive and gram negative bacteria. It was observed that the phytochemically reduced RGO shows significant antibacterial activity.